Design, Synthesis, and Evaluation of Organic and Organometallic Pyrazoline Derivatives as Selective Dual COX-2/5-LOX Inhibitors and Potential Anticancer Agents - Mascayano-Collado, C; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Morales, P (American Chemical Society, 2026)
Inspired by the structure of the anti-inflammatory drug Celecoxib, which is currently used in cancer prevention and treatment, we report the design, synthesis, and biological evaluation of organic and organometallic molecular hybrids based on pyrazolines (4a-h). Structure-Activity Relationship (SAR) analyses showed that the combination of catechol-benzenesulfonamide in 4a (organic) and 4c (ferrocenyl) derivatives acts as potent and highly selective dual inhibitors (IC50 COX-2 = 4.58 and 2.88 mu M; IC50 5-LOX = 0.23 and 0.10 mu M, respectively; evaluated against COX-1 and 15-LOX isoforms). Molecular dynamics simulations of 4a and 4c in 5-LOX showed their preferential localization at the allosteric site and at the entry channel, respectively, consistent with their noncompetitive (4a) and mixed (4c) kinetics. Furthermore, the noncytotoxic complex 4c (MRC-5, CC50 = 38.13 mu M) exhibited anticancer effects in ovarian cancer cells (A2780, CC50 = 13.79 mu M) that overexpress the proinflammatory enzymes COX-2 and 5-LOX (Western Blot), exceeding the activity of the drug Celecoxib.